They Sent Me There to Die - Koleilat, Issam (Ars Medica, 2020)
Excerpt: “They sent me there to die.” He looked up at me, a man of no more than maybe 52 years. He, like many, had been tricked and conned and likely socially pressured into a tobacco addiction before the medical outcry once the long-term effects of nicotine became known and widely publicized. And as so many before him, he developed complications.